Defining Clinical Course of Patients Evaluated for Pediatric Acute-Onset Neuropsychiatric Syndrome: Phenotypic Classification Based on 10 Years of Clinical Data - Masterson, Erin E.; Miles, Kate; Schlenk, Noelle; Manko, Cindy; Ma, Meiqian; Farhadian, Bahare; Chang, Kiki; Silverman, Melissa; Thienemann, Margo; Frankovich, Jennifer (Developmental neuroscience, 2025)
Abstract Introduction: Establishing clear and standardized terminology regarding disease state and course is crucial for enhancing communication, research, and treatment decisions, particularly when there are no clearly identified biological markers, as in the case of pediatric acute-onset neuropsychiatric syndrome (PANS). We aim to propose terminology for assessing disease state and classifying long-term clinical courses in individuals evaluated for PANS, advancing standardization in clinical care and research. Methods: We drew upon clinical expertise, insights from similar conditions, and a decade of longitudinal clinical data from the Stanford University Immune Behavioral Health (IBH) Clinic to devise terminology for characterizing patient status and clinical progression among patients evaluated for PANS. Utilizing parent- and clinician-reported data spanning from 2012 to 2023, we constructed a comprehensive dataset documenting patients’ disease trajectory from initial flare to latest clinical encounter, encompassing intervening recovery periods. This allowed us to apply the proposed terminology to the IBH Clinic patient cohort, offering a detailed phenotypic analysis of PANS flares and clinical courses. Results: We analyzed 264 patients evaluated for PANS at the IBH Clinic and stratified them based on whether they met PANS criteria at initial flare (51%), after initial flare (24%), or had not met criteria at the time of analysis (25%). The average age at the initial flare ranged from 6.1 to 8.3 years across these patient subgroups. Among patients with PANS, the average isolated flare lasted 3.7–4.1 months and 95% of flares resolved within 1 year. Five years after initial flare, most (77%) patients with PANS had had multiple flares, and nearly half (43%) had experienced a flare that lasted >12 months, approximately half of which occurred at the initial flare. Conclusions: Patients evaluated for PANS at the IBH Clinic showed diverse clinical presentations and illness courses over the long term, with most experiencing a relapsing-remitting clinical course but some exhibiting persistent symptoms. Many experienced neuropsychiatric flares before meeting PANS classification criteria. This underscores the importance of clinicians being vigilant for new neuropsychiatric symptoms in pediatric patients, even if they do not immediately meet PANS criteria. Based on these data, we propose terms and definitions for characterizing patient status, flares, and clinical course, which we hope the clinical and research communities will build on and refine.